The Integration of Digital Transformation and e-WOM on Consumers in the Religious Tourism Industry - Azzahra, Alifya; Ramadhan, Novitha Dwipermata; Yoestini; Dirgantara, I Made Bayu (Economic and Business Horizon, 2025)
The rapid advancement of digital technology has catalyzed transformation across various sectors, including the religious tourism industry, particularly in Umrah and Hajj services. One key adaptation to this digital shift is the implementation of electronic word of mouth (eWOM) as a strategic marketing tool aimed at influencing consumer purchase intention. This study seeks to explore the interrelationship between digital transformation, eWOM, and purchase intention within the context of religious tourism by employing a Systematic Literature Review (SLR) approach. A comprehensive analysis of both national and international scholarly literature was conducted to identify core concepts and examine their interlinkages. Through a thorough theoretical examination, this study aims to contribute to the development of sustainable digital marketing strategies and provide a conceptual foundation for future research in this domain. The findings reveal that eWOM exerts a significant influence on purchase intention, both directly and indirectly through the mediating roles of brand image and trust. These insights highlight the strategic importance of integrating digital innovation with sustainable marketing practices to enhance the competitive advantage of Umrah and Hajj travel agencies in the digital era.